Kajian Keberkesanan Pembelajaran Interaktif Berasaskan Aplikasi Kahoot:: A Case Study of the Principles of Marketing Course - Che In, Faridah; Ahmad , Afzam Zulhusmi (Online Journal for TVET Practitioners, 2019)
Nowadays, the use of game elements is used in various contexts for various purposes. Game in the form of online is one of the alternative methods in the teaching and learning of this 21st century student. Kahoot is one of the methods in interactive learning today. It is an alternative method that can increase the motivation of students in the classroom. The aim of this study was to examine the effectiveness of this method to the students who take the course of marketing principles to solve problems in understanding the content of the topics of marketing mix. A total of 40 students were involved in this study. As a result of a preliminary survey conducted through theory test in the classroom, the previous results obtained by the students were at an unsatisfactory level. Research conducted over the last semester and has shown encouraging results for students and lecturers. The use of the Kahoot portal in the form of online exercises, reviews and assignments has shown students to be more excited and excited to learn the marketing mix. The use of the Kahoot portal in the form of online exercises, reviews and assignments has shown students to be more excited and excited to learn the marketing mix. The findings showed that there was an increase in student achievement and found that the comparison of the results between the Pre-Action and Post-Action Test on these 40 students had increased relatively. In addition, the findings from the questionnaire were also carried out that students also showed a tendency and interest in the teaching methodology. Hence, this online game teaching method can be seen as one of the most effective methods of teaching and learning in the R & D (Learning and Teaching) sessions, especially in the course principles of marketing.